Modelo de parceria entre comitê paralimpico brasileiro e centro de traumatologia do esporte: centro de referência em desenvolvimento de halterofilismo. - Spina, Murilo Arsenio [UNIFESP] (2018)
Introduction: Weightlifting is one of the fastest growing modalities in the Paralympic movement in the world. Following this trend, in Brazil we also observed a growing increase in the number of athletes participating in the modality in the national circuit. In this way we observe the need for a Reference Center for the development of the modality where the clubs, athletes and professionals involved can seek information about the modality. The present report explains the actions, objectives and impact of the partnership project "Center of reference in development of weightlifting", destined to the people in conditions of physical disability. The viability since the partnership project arises from a technical cooperation agreement between the Brazilian Paralympic Committee and the Sports Medicine Center UNIFESP. Regionalization a Reference Center on Weightlifting Development starts from a principle that includes a strategy to establish the possibility of people with physical disabilities start their sports practice offering a structure of technical cooperation of different professionals. The objective of the present work is to present an interaction of efforts between the parties for the creation and maintenance of the Center of Developmental Reference (CRD) of Weightlifting, through activities of development and development of the modality. Methods: In order to carry out the project, a space was made available at the CETE / Clube Escola rehabilitation center, where it was equipped by the Brazilian Paralympic Committee with specific bodybuilding equipment for the practice of the modality. This practical environment was coupled with the academic part of CETE's sports medicine for outpatient care, assessments and research projects. Thus, we can offer an environment where the athlete has an ambulatory assistance, training and research development related to the modality. Results: In front of the work carried out in the Reference Center, we conducted four training phases of the Brazilian team (2016/2017); 4 acclimatizations of the Brazilian team for international competitions (Rio 2016 Word Cup, Rio 2016 Paralympic Games, Parapan Youth Sao Paulo 2017, Word Cup Hungary 2017); 1 Acclimatization and International Training Athlete Osmar Sheriff Egypt; 1 update course in Resisted Exercises 2017; 1 Specialization course in resisted exercise physiology in applied bodybuilding in the health area and injury prevention.2018; 1 Paper presented at the Brazilian Congress of Shoulder Surgery; 1 publication Brazilian Journal of Orthopedics; 1 publication National Rehabilitation Magazine, 1 Paper presented at an International Congress of Sport adapted Colombia, besides offering support to scientific research, totaling 2 undergraduate, 1 specialization, 3 master's, 1 doctorate and 4 postdoctoral studies. Conclusion: At the end of this study, we conclude that for the effective development of a partnership that uses the paradesport it would be necessary to use science through research. In this sense transfer the knowledge of the university to society and into the academic universe relevant problems of society as a way to contribute to the development of weightlifting. This healthy relationship has enabled professionals to improve in their specific areas and thus offering all technical support, management and training to complement the paradesport.